PEMANFAATAN AGEN HAYATI DALAM BUDIDAYA TITONIA PADA ULTISOL - Auzia Asman; Nurhajati Hakim; Agustian Agustian; Hermansah Hermansah (Jurnal Ilmu Tanah dan Lingkungan, 2008)
Titonia could be used as alternative fertilizer to reduce up to 50% the chemical fertilizer aplication of chili, gardamon, maize, soybean and sweet potato. The titonia which grow as alley croping system(20 rows ha-1) could produced 6,6 -6,8 ton ha-1 y-1 of dry biomass with 2 months pruning period. This amount equal to 40 ton ha-1 y-1 of fresh biomass of titonia. Such amount of biomass content 150-240 kg ha-1 y-1 of N and 156 – 245 kg of K that could be used to replace the 50 % of chemical fertilizer. In the rhizosphere of titonia was observed the micro organism has role in increasing the production of biomass such as micorhizae, bacteria diluted P, Azotobacter, Azospirillium, and bacteria produced of phitohormon. We assume that the re-inoculation of those microorganism in to the rhizosphere of titonia might contribute in increasing of titonia biomass and nutrients yield. The study of the re-inoculation of such microorganism to the rhizosphere of titonia in order to find out the kind of micro organism which highly contributed in increasing of biomass was conducted. The study was conducted by using completed randomized designed with10 treatments and 5 replications. Those treatments are A=without reinoculation (control); B=bacteria diluted phosphate (bdp); C=Azotobacter; D=Azospirillium; E=bacteria produced phytohormon (bph); F=bdp+Azotobacter; G=bdp+Azospirillium; H=bdp+bph; I=bdp+Azotobacter+Azospirilliun; J=bdp+Azotobacter+Azosprilliun + bph. The result of study showed the combination of the reinoculation to the rhizospehere in increasing of biomass and nutrients yield of titonia were (1)Bacteria diluted phosphate; (2) Azospirillium; (3) Bacteri diluted phosphate + Azototobacter; (4) Bacteria diluted phosphate +Azospirillium; dan (5) Bacteria diluted phosphate +Azotobacter +Azospirillium.Keywords: Agen Hayati, Titonia, alternative fertilizer